Método, evolución y progreso en la ciencia - Sergio Martínez (Crítica)
In this paper I address the problem of characterizing a notion of scientific or cognitive progress. I show that there is a close connection between the different characterizations of scientific method and notions of progress. Until the early sixties, a very common (often implicit) assumption was that progress could be understood as a by-product of the use of the scientific method. The work of Thomas Kuhn made clear that such a simple minded characterization of progress could not be right. I examine a series of attempts aiming to spell out a notion of scientific progress, and argue that an underlying assumption of these proposals is an assumption about the underlying methodological unity of science.